Livelihood coping strategies of women heads of households in Cairo's informal settlements: The case of Izbet El Haggana - Rafea, Nora (AUC Knowledge Fountain, 2017)
This study investigates the livelihood coping strategies of women heads of households in Cairo’s informal settlements. Its research problem centers on the premise that urban poverty is underestimated in Egypt, in addition, the growing rate of ‘urbanization’ is increasing the vulnerability of women heads of households. The study is focused on Cairo’s informal areas as they represent a shelter for millions of rural migrants to the city. Informal areas in Cairo generally called “ashwa’eyat” in Arabic are either stigmatized or rationalized, yet, the nature of their informality and proximity to the urban center, and sometimes, even government establishments make them a unique source for inquiry. The main research question that is posed by this research is an attempt to understand the impact of the vulnerable context on the livelihood coping strategies of women heads of households in those spaces that are autonomous from the state. This question is important in light of a historical moment in the Egypt that is challenging the relationship between the state and society, and the choice of this specific group is important because women face “double marginalization” in a vulnerable urban context. The thesis is using the sustainable livelihood approach as the foundational theoretical framework in approaching the subject of women heads of households in Cairo’s informal settlements that fits under the bigger context of urban poverty. The study used a qualitative approach in gathering data from Izbet El Haggana, the study area and one of Cairo’s largest informal settlements.